Implementation of the SIUUL Model in Developing English MC Skills in English Education Study Programs - Ahmad Fauzy Hamdi; Devini Aulya Rahman; Henny Henny; Wahyuni Wahyuni; Sri Watini (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to describe the implementation of the SIUUL Model which was carried out in the MC training for English education study program students at Panca Sakti University Bekasi. Using a qualitative descriptive research method. Data obtained through observation, interviews and documentation. Research subjects were students majoring in the English education study program at Panca Sakti University Bekasi. The results of the study found that the MC training in the English education study program at Panca Sakti University had well implemented the SIUUL model in accordance with the principles and stages of the model.